Forests and climate change adaptation policies in Cameroon - Bele, M.Y.; Somorin, O.A.; Sonwa, D.J.; Nkem, J.; Locatelli, Bruno (Springer, 2011)
Nowadays, adaptation has become a key focus of the scientific and policy-making communities and is a major area of discussion in the multilateral climate change process. As climate change is projected to hit the poorest the hardest, it is especially important for developing countries to pay particular attention to the management of natural resources and agricultural activities. In most of these countries such as Cameroon, forest can play important role in achieving broader climate change adaptation goals. However, forest generally receives very little attention in national development programme and strategies such as policy dialogues on climate change and poverty reduction strategies. Using a qualitative approach to data collection through content analysis of relevant Cameroon policy documents, the integration of climate change adaptation was explored and the level of attention given to forests for adaptation analysed. Results indicate that, with the exception of the First National Communication to UNFCCC that focused mostly on mitigation and related issues, current policy documents in Cameroon are void of tangible reference to climate change, and hence failing in drawing the relevance of forest in sheltering populations from the many projected impacts of climate change. Policies related to forest rely on a generalized concept of sustainable forest management and do not identify the specific changes that need to be incorporated into management strategies and policies towards achieving adaptation. The strategies and recommendations made in those documents only serve to improve understanding of Cameroon natural resources and add resilience to the natural systems in coping with anthropogenic stresses. The paper draws attention to the need to address the constraints of lack of awareness and poor flow of information on the potentials of forests for climate change adaptation. It highlights the need for integrating forest for adaptation into national development programmes and strategies, and recommends a review of the existing environmental legislations and their implications on poverty reduction strategy and adaptation to climate change